Reclaiming Islamic Educational Identity through Curriculum: A Critical Analysis of Adabul ‘Alim wal Muta’allim in Pesantren Tebuireng - Jasminto, Jasminto; Rofi’ah, Siti; Amayreh, Muath Khalil (International Journal of Religion and Social Community, 2025)
This study aims to explore the process of reconstructing Islamic educational identity carried out by Pesantren Tebuireng through the development and implementation of a curriculum based on traditional values contextualized for the modern era. The main focus of this research is the classical text Adabul ‘Alim wal Muta’allim by Hadratus Syaikh Hasyim Asy’ari, a foundational work that holds a significant position within the pesantren tradition as a reference for ethics and pedagogy. Using a qualitative method with textual and contextual approaches, this research traces how the noble values contained in the text are reinterpreted to address the challenges of modern education. Data were collected through comprehensive literature studies and in-depth interviews with caretakers, teachers, and curriculum developers within the Pesantren Tebuireng environment. The findings indicate that Adabul ‘Alim wal Muta’allim functions not only as a moral guideline in the teacher-student relationship but also as a strategic tool for character formation, the strengthening of spirituality, and the development of students’ integrity. Universal values such as sincerity, humility, responsibility, and proper conduct in the pursuit of knowledge are integrated into a curriculum framework that is relevant to contemporary developments. This curricular strategy demonstrates that Pesantren Tebuireng is not merely preserving tradition but is consciously and purposefully transforming education. Thus, the pesantren is able to build an Islamic educational identity that is dynamic, contextual, and firmly rooted in Islamic values, while also actively responding to current social and intellectual challenges.